The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/ecc.13212
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress at hospital admission is related to symptoms severity and health status in malignant pleural effusion patients

Abstract: Objective The incidence and associated healthcare costs of malignant pleural effusion (MPE) are expected to rise, but there is limited evidence about which factors affect patients' prognosis. So, the aim of this study was to determine whether psychological distress at hospital admission is associated with symptom severity and health status in patients with MPE. Methods A longitudinal observational prospective cohort study was carried out in the Pulmonology Service of the Granada University Hospital Complex in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Second, the lack of a structured psychiatric clinical interview to assess depression and anxiety is also one of the limitations. Nevertheless, previous studies have used the HADS to evaluate the presence of psychological distress [ 11 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the lack of a structured psychiatric clinical interview to assess depression and anxiety is also one of the limitations. Nevertheless, previous studies have used the HADS to evaluate the presence of psychological distress [ 11 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…LC patients present various symptoms, such as pain, coughing, fatigue and shortness of breath in the early stages after surgery or even a long time after surgery [8][9][10]. Moreover, patients with lung cancer experience a variety of distressing symptoms, many of which begin before diagnosis and continue throughout the course of the disease and its treatments, adversely affecting functional status and quality of life (QOL) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the lack of a structured psychiatric clinical interview to assess depression and anxiety. Nevertheless, previous studies have used the HADS to evaluate the presence of psychological distress [63,11].…”
Section: Discussionmentioning
confidence: 99%
“…LC patients present various symptoms, such as pain, coughing, fatigue and shortness of breath in the early stages after surgery or even a long time after surgery [8,9,10]. Moreover, patients with lung cancer experience a variety of distressing symptoms, many of which begin prior to diagnosis and continue throughout the course of the disease and its treatments, adversely affecting functional status and quality of life (QOL) [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Handgrip strength has been recognized as a valuable indicator of overall muscular strength and is associated with a variety of health outcomes, including mortality, morbidity, and functional decline in diverse populations [ 35 ]. Several studies have demonstrated the significance of handgrip strength as a predictor of various health-related events, such as cardiovascular events, disability, and frailty [ 36 ]. Given its simplicity, portability, and ability to reflect broader aspects of health, handgrip dynamometry has become an integral component of clinical assessments and research investigations aimed at understanding and monitoring individuals’ health status.…”
Section: Methodsmentioning
confidence: 99%